2019
DOI: 10.11648/j.jfa.20190703.11
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Improvements of Post-Acquisitions Corporate Performance in Industrial Sector in the Egyptian Stock Market

Abstract: The purpose of this study is to examine the impact of Egyptians Acquisitions on the post-performance of the acquired companies from the period of 2003 to 2015 by the use of event study methodology. This is done by studying the financial post-performance (includes: liquidity, activity, profitability and capital structure ratios) of a sample consists of 17 companies from the industrial sector as dependent variables, and comparing their results with the pre-performance and the acquisition event as an independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It seems to support Modogliani and Miller (1958) postulation that capital structure of entities is irrelevance. However, the result did not support Lukman (2020),Abanum & Ebiaghan (2022) Abdelrahman and Elgiziry (2019), Akpan et al, (2018), andDaniya et al, (2016) that found positive and significant change in capital structure due to merger and acquisition. The result probably suggests that the consolidation has pulled funds from merged banks, and less reliability on debt (Tarila & Ogege, 2019;Taiwo & Musa, 2014).…”
Section: 52mentioning
confidence: 71%
“…It seems to support Modogliani and Miller (1958) postulation that capital structure of entities is irrelevance. However, the result did not support Lukman (2020),Abanum & Ebiaghan (2022) Abdelrahman and Elgiziry (2019), Akpan et al, (2018), andDaniya et al, (2016) that found positive and significant change in capital structure due to merger and acquisition. The result probably suggests that the consolidation has pulled funds from merged banks, and less reliability on debt (Tarila & Ogege, 2019;Taiwo & Musa, 2014).…”
Section: 52mentioning
confidence: 71%